Immobilization of lipases via interfacial activation on hydrophobic supports: Production of biocatalysts libraries by altering the immobilization conditions - Peña, Sara Arana; Rios, Nathalia Saraiva; Carballares, Diego; Gonçalves, Luciana Rocha Barros; Lafuente, Roberto Fernandez (Catalysis Today, 2021)
Lipases A and B from Candida antarctica (CALA, CALB), and those from Candida rugosa (CRL) and Rhizomucor miehei (RML) have been immobilized on octyl agarose beads under 16 different conditions. The activities of the biocatalysts versus different substrates were analyzed, as well as their thermal stabilities at pH 7.0. All CALB and CRL preparations showed very similar properties, except the CRL biocatalysts prepared at pH 9. Under these conditions the free enzyme was partially inactivated. Immobilized CALA showed some significant differences in activity depending on the immobilization conditions when using esters of mandelic acid as substrates (the activities of the different preparations differed by more than a 2-fold factor), while when using the other substrates the differences were minimal. However, immobilized RML enzyme greatly alters its activity depending on the immobilization conditions, reaching differences up to 4–5 fold in both activity and stability. It is remarkable that the effect of one immobilization variable depends on the substrates, and that there are strong interactions between the different immobilization variables. Thus, this immobilization method was very robust (producing almost identical functional biocatalysts independently from the immobilization conditions) using CRL or CALB, while the immobilization conditions must be carefully controlled using RML to have reproducible results 2030-12